A proposed biomass char classification system - Lester, Edward; Avila, Claudio; Pang, Cheng Heng; Williams, Orla; Perkins, Joseph; Gaddipatti⁠, Sanyasi; Tucker, Gregory A.; Barraza, Juan Manuel; Trujillo-Uribe, María Patricia; Wu, Tao (Elsevier, 2018)
A new classification system is proposed for the morphological characterisation of char structures from biomass. These char structures are unlike the coal chars that have an established nomenclature via the International Committee of Coal and Organic Petrology (ICCP) which divides char structures into thin walled and thick walled spheres and networks, mixed dense and mixed porous, fusinoids and solids. The chars from biomass show a tendency, depending on heating regime, to produce different types of internal pore structure (cellular and porous) and aspect ratio (high and low) compared with coal chars. For this reason a new classification system has been developed to cover these new structures which should assist in combustion, co-firing and gasification research where these intermediate char structures play an important role in conversion efficiency. Low heating rates (using a muffle furnace at 1000°C and 3min) were used to create chars from 9 different biomass types, with a range of lignocellulosic compositions. Char type appeared to depend on the biomass type itself and original lignocellulosic composition (cellulose, lignin and hemicellulose content) and cell structure.